S108 Primary care re-consultation after community acquired pneumonia: a large population-based cohort study. (12th November 2019) - Baskaran, V; Lim, WS; McKeever, T
Abstract : Introduction: There is paucity of information on the burden of disease during recovery from community acquired pneumonia (CAP). This study aims to describe healthcare re-consultation episodes within 30 days after a diagnosis of CAP. Methods: Adults aged ≥18 with the first CAP Read code recorded in Clinical Practice Research Datalink (CPRD) GOLD between July 2002 and June 2017 were included. Patients were followed up to 30 days from date on which CAP Read code was recorded (index date). Re-consultation was defined as recording of any medical Read codes (excluding admin-related codes) after the index date; re-consultation was counted as a single episode if there were multiple Read codes recorded in a day per patient. Statistical analyses were performed using Stata/MP15. Results: There were 135232 patients with CAP. Thirty-day mortality was 6.7% (n=9004). Excluding patients who died, 41.7% (n=52689) had re-consulted primary care at 30 days for any reason. In comparison to the 18–49 age group, the 50–64 (OR 1.35, 95% CI 1.30–1.40) and 65–74 (OR 1.32, 95% CI 1.27–1.37) age groups were more likely to re-consult whilst those ≥ 85 (OR 0.65, 95% CI 0.64–0.68) were less likely to re-consult. Females were less likely to re-consult (OR 0.95, 95% CI 0.93–0.98). Compared to never smokers, current smokers (OR 1.14, 95% CI 1.11–1.18) and ex-smokers (OR 1.19, 95% CI 1.16–1.23) were more likely to re-consult. Of those who re-consulted, 43.7% (n=23036) re-consulted primary care twice or more. Forty-one percent (n=21533) of these patients re-consulted for a respiratory reason whilst a low proportion re-consulted for a cardiac reason (8.3%, n= 4359). At re-consultation, 26.8% (n=14138) received a further course of antibiotics. Most of these patients (77.5%, n=10955) received one course of antibiotics within 30 days of CAP. Penicillins (39.7%, n=7820) and macrolides (25.9%, n=5088) were the commonest antibiotics prescribed. Conclusion: A significant proportion of patients, particularly those aged 50–75 years re-consult primary care after CAP. More than one re-consultation is common, highlighting the burden on primary care. When re-consultation occurs, >25% patients are prescribed a further course of antibiotics, therefore emphasizing the importance of promoting antibiotic stewardship.